Pilot study of patron sound level exposure in loud restaurants, bars, and clubs in New York city. Issue 7 (3rd July 2017) - Spira-Cohen, Ariel; Caffarelli, Anna; Fung, Lawrence
ABSTRACT: Visiting restaurants, bars, clubs, and lounges is a regular part of urban cultural life for residents and tourists alike; however, anecdotal reports and diner surveys suggest that sound levels are excessive and diners dislike them. High sound levels in these venues can contribute to both patron and employee overexposure, and young people may be particularly at risk. To supplement the paucity of literature and data on noise in urban venues, patron noise exposure was measured inside a sample of loud New York City restaurants, bars, clubs, and lounges. Sound level measurements were obtained in 59 venues. Field staff conducted one 20–162 minute visit per venue on a Thursday, Friday, or Saturday evening. The equivalent continuous sound pressure level on the A-scale (LAeq ) was calculated for each visit. Median and mean LAeq among all venues sampled were both 92 decibels (dBA). Clubs and lounges had a higher mean LAeq than restaurants and bars (97 vs. 91 dBA, p < 0.05). A greater number of patrons was associated with a higher LAeq . Higher LAeq values were observed during later hours of the evening (9 PM and later). For 80% (N = 47) of the venues, the LAeq was above 85 dBA. In 49% (N = 29) of the venues, the visit exceeded the maximum allowable daily noise dose based on National Institute of Occupational Safety and Health (NIOSH) Recommended Exposure Limit (REL) of 85 dBA 8-hr Time-Weighted Average (TWA). Venues should assess indoor sound levels including employee exposure and aim to maintain sound levels that are within NIOSH guidelines.